The adaptable Jesus of the fourth gospel : the pedagogy of the logos - Sturdevant, Jason S. (Novum Testamentum, Supplements, 2015)
In The Adaptable Jesus of the Fourth Gospel , Jason S. Sturdevant argues that the Gospel of John portrays Jesus as an adaptable teacher, who accommodates to different people in various ways to a singular end, to bring each to faith. In the same way, the Logos accommodates to humanity via the incarnation. Adaptability serves as both an interpersonal and universal category. Early Christian interpretations of John, especially that of John Chrysostom, describe the Jesus of John by echoing characterizations of the ideal Greco-Roman pedagogue, adapting to his diverse students. By looking to such interpretations, as well as illumination from the milieu of the Fourth Evangelist, Jason S. Sturdevant provides a new lens through which to understand the characterization of the Johannine Jesus.